Modern Adonis. (London : Male Classics Ltd., 1966)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : tweemaandelijks
Redactie : 15 Kensington High Street, London W8
Engels
Periodiek